Cortisol metabolism, postnatal depression and weight changes in the first 12 months post-partum. - Rogers, S; Hughes, B; Tomlinson, J; Blissett, J (Wiley, 2016)
Background and Objectives Postnatal depression correlates with postpartum weight retention, and dysregulated cortisol metabolism is evident in depressed individuals. Cortisol metabolism, BMI and metabolic phenotype are robustly associated but the role of cortisol metabolism in postnatal mental health and weight loss has never been examined. Design A longitudinal observation. Patients 49 healthy women with uncomplicated pregnancy. Measurements BMI and urinary steroid metabolites at 1 week and 1, 3, 6 and 12 months postpartum. Validated urinary steroid metabolite ratios were measured to determine the activities of 11β-hydroxysteroid dehydrogenases (11β-HSD) that interconvert inactive cortisone and active cortisol and the 5α-reductases that clear cortisol to its inactive metabolites. Postnatal depression symptoms were measured at 1, 6 and 12 months. Results Low 5α-reductase activity was associated with greater weight loss across the first year, independent of demographics, breastfeeding and depression. Postpartum BMI change was unrelated to postnatal depression at any time. Symptoms of postnatal depression were related to higher cortisol metabolite production at 12 months, independent of demographics and breastfeeding. Conclusions Greatest weight loss in the postpartum year was associated with lower conversion of cortisone to cortisol and lower conversion of cortisol to its metabolites, supporting previous work that demonstrates the facilitative role of lower 5α-reductase and 11β-HSD-1 in weight loss. Greater depression symptoms were associated with higher cortisol metabolite production rates. Whilst weight and mental health are both associated with dysregulation of the HPA axis, there may be different pathways towards depressed and obese phenotypes in healthy postpartum samples.